International Aid and Its Role in Shaping Agriculture Policy Narratives in Ghana - James Boafo; Kristen Lyons; Senyo Dotsey (Africa Spectrum)
International aid in the form of development assistance helps developing countries meet their development needs. Aid is also used as a conduit to drive the interests of donor countries in recipient countries. In Ghana, there is a renewed interest from donors to drive agriculture transformation through investment in market-based policies. However, little is known about how development assistance is used by donor countries to promote their interests in the Ghanaian agriculture sector. This article draws on policy documents and interviews with policy actors and donor stakeholders to understand the processes and outcomes of agriculture sector policymaking in Ghana. Our findings demonstrate the ways financial, technical, and other resources are deployed by donors to shape agricultural policy outcomes. We further demonstrate how donors promote market-based solutions in the agriculture sector. We conclude by reflecting on the limits of these donor-led agricultural policies in meeting the needs of Ghana's smallholder farmers.